Impaired degradation of serum amyloid A (SAA) protein by cytokine-stimulated monocytes - Migita, K (Blackwell Science Inc, 2001)
Secondary amyloidosis (AA amyloidosis) is a systemic disease characterized by the extracellular tissue deposition of insoluble amyloid A (AA) protein. Aberrant metabolism of serum amyloid A (SAA) by macrophages is only one of many putative mechanisms which may be important in AA amyloidogenesis. In this study, we investigated the effects of cytokines on human monocyte-mediated SAA proteolysis. Human peripheral blood mononuclear cells (PBMC) or CD14(+) monocytes were cultured with SAA, and the culture supernatants were then subjected to anti-SAA immunoblot. CD14(+) monocytes degraded SAA completely. Whereas, when CD14(+) monocytes were pretreated with IL-1β or IFN-γ, increasing amounts of SAA-related derivatives were detected in culture supernatants. These findings suggest that activation of monocytes by IL-1β or IFN-γ hampers the proteolysis of a precursor protein and leads to a partial degradation of SAA. This down-regulated proteolysis of SAA protein by cytokine-stimulated monocytes may play a role in the mechanism of AA amyloid formation as well as its removal.